THE STUDY OF PHTHALATES MIGRATION IN WINE PRODUCTS BY GC-MS METHOD - Gh. Duca; R. Sturza; D. Lazakovich (Chemistry Journal of Moldova: General, Industrial and Ecological Chemistry, 2012)
A number of studies have shown phthalates’ potential impact on human health due to their carcinogenic and endocrinedisrupting effects. More than 2000 analyses for determination of phthalates’ rests in alcoholic beverages were done in the laboratory of National Center for Quality Testing of the Alcoholic Beverages (Republic of Moldova) using modern method of analysis like GC-MS. This article is an extended abstract of a communication presented at the Conference Ecological Chemistry 2012